Interstitial lung disease in infancy. (November 2020) - Bush, Andrew; Gilbert, Carlee; Gregory, Jo; Nicholson, Andrew Gordon; Semple, Thomas; Pabary, Rishi
Abstract: There is a wide differential diagnosis of early onset respiratory distress especially in term babies, and interstitial lung disease (chILD) is a rare but important consideration in this context. chILD manifesting immediately after birth is usually related to mutations in surfactant protein genes, or conditions related to the Congenital Acinar Dysplasia -Alveolar capillary dysplasia - Congenital Alveolar Dysplasia (CAD-ACD) spectrum. There is currently no specific treatment for these conditions, and management is supportive. Prognosis is very poor in most of these babies if onset is early, with relentless respiratory deterioration unless transplanted. Ideally, the diagnosis is made on genetic analysis, but this may be time-consuming and complex in CAD-ACD spectrum, so lung biopsy may be needed to avoid prolonged and futile treatment being instituted. Milder forms with prolonged survival have been reported. Early onset, less severe chILD is usually related to neuroendocrine cell hyperplasia of infancy (NEHI), pulmonary interstitial glycogenosis (PIG) and less severe disorders of surfactant proteins. PIG and NEHI are not specific entities, but are pulmonary dysmaturity syndromes, and there may be a number of underlying genetic and other cause. If the child is stable and thriving, many will not be subject to lung biopsy, and slow improvement and weaning of supplemental oxygen can be anticipated. Where possible, a precise genetic diagnosis should be made in early onset cHILD allow for genetic counselling. chILD survivors and their families have complex respiratory and other needs, and co-ordinated, multi-disciplinary support in the community is essential.